P194 Epivin: a phase II double-blind randomised control trial investigating the use of epigallocatechin-3-gallate (veregen®, catephen®) vs placebo in the treatment of usual-typed vulval intraepithelial neoplasia. (1st November 2019) - Yap, J; Slade, D; Fox, R; Kaur, B; Hughes, A; Ganesan, R; Velangi, S; Luesley, D
Abstract : Introduction/Background: We have shown that Epigallocatechin-3-gallate (EGCG) targets the human papillomavirus (HPV)-encoded E6 and E7 oncoproteins for degradation, resulting in epithelial cell growth inhibition in in vitro models. Recent clinical trials indicated that Veregen®, a topical ointment containing 55–72 mg of EGCG, is a safe and effective treatment for vulval warts, benign lesions caused by low-risk HPV strains. Based on our findings, we undertook a phase II randomised control trial (RCT) to evaluate if Veregen® is also effective in the treatment of usual-type vulvar intraepithelial neoplasia (uVIN), a pre-malignant lesion associated with high-risk HPV infection. Methodology: Eligible patients were randomised to receive either Veregen® or placebo ointment (applied 3 times daily for 16 weeks), and were followed up at 2, 4, 8, 16, 32 and 52 weeks. Outcome measures, recorded at 16 and 32 weeks, were histological (HR) and clinical (CR) response (measured by ≥30% reduction in the sum of the longest diameter of all lesions when compared to baseline) and toxicity. The primary outcome, HR, required a difference in the number of responders ≥3 in favour of Veregen® to detect a difference of 20% between groups (10% for placebo and 30% for Veregen®), as per Jung's design with type I, II errors ≤0.15. Results: 26 patients were randomised, all 13 patients who received Veregen® showed either complete (n=5) or partial (n=8) CR. In placebo group, 3 patients had complete CR, 2 had partial CR and 6 had stable disease. Patients in the Veregen® group showed significant improvement in CR as compared to the placebo group (P=0.0026). There was no evidence of difference in HR and toxicity reported in both groups. Conclusion: This study indicates that Veregen® application is safe and leads to at least a partial clinical resolution of uVIN lesions, thus warranting a phase III multi-centre RCT. Disclosure: The study is funded by the National Institute for Health Research via the Research for Patient Benefit programme and Medigene AG supplied Veregen® and placebo.